Keheningan menurut Henri Nouwen dalam Dunia Modern - Saputra, Memet (Felicitas, 2024)
This study focuses on understanding the concept of silence according to Henri Nouwen and its relevance to spiritual life in the modern era. The research aims to explore Nouwen's idea of silence, which is often equated with solitude or loneliness. However, silence is a distinct concept that plays a crucial role in fostering spiritual growth. In contemporary times, we are inundated with a constant flow of information through digital devices and media platforms, a hallmark of the modern age. Consequently, we often find ourselves too busy and struggle to carve out moments of stillness and tranquility. Such conditions, sooner or later, can hinder the development of spiritual life. This paper examines the relevance of silence in the modern world and provides practical ways to integrate it into daily life. The methodology employed is a literature review, analyzing Nouwen's writings and other relevant sources from books and journals on modern life. The findings reveal that silence is essential and can be meaningfully practiced in today's modern context.